2004
DOI: 10.1097/01.ju.0000143930.73016.c6
|View full text |Cite
|
Sign up to set email alerts
|

Hip Fractures in Men With Prostate Cancer Treated With Orchiectomy

Abstract: Hip fracture risk increases almost immediately following orchiectomy and the excess risk persists for at least 15 years. This side effect should be considered when assessing the merits of androgen deprivation therapy, particularly in symptom-free men diagnosed with localized prostate cancer. Measures to prevent osteoporosis should be considered in men undergoing androgen deprivation therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
4

Year Published

2006
2006
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 16 publications
1
27
0
4
Order By: Relevance
“…Furthermore, localised prostate cancer may be associated with a prolonged survival [43] and thus a sustained risk of even late metastases to the skeleton and detrimental effects of long-term androgen deprivation therapy [1,44]. Dickman et al [45] reported an early and sustained increase in the risk of hip fractures in patients who underwent bilateral orchiectomy for prostate cancer, In our study the increase was seen later in the cause of the prostate cancer and this may be due to the fact that not all patients underwent orchiectomy or received androgen deprivation therapy. Furthermore, patients treated with orchiectomy may have more advanced prostate cancer than those not undergoing orchiectomy, and this may also contribute to the differences between our results and those of Dickman et al [45].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, localised prostate cancer may be associated with a prolonged survival [43] and thus a sustained risk of even late metastases to the skeleton and detrimental effects of long-term androgen deprivation therapy [1,44]. Dickman et al [45] reported an early and sustained increase in the risk of hip fractures in patients who underwent bilateral orchiectomy for prostate cancer, In our study the increase was seen later in the cause of the prostate cancer and this may be due to the fact that not all patients underwent orchiectomy or received androgen deprivation therapy. Furthermore, patients treated with orchiectomy may have more advanced prostate cancer than those not undergoing orchiectomy, and this may also contribute to the differences between our results and those of Dickman et al [45].…”
Section: Discussionmentioning
confidence: 99%
“…Cette diminution s'accompagne d'une augmentation significative de la survenue de fractures : dans une large étude Medicare incluant 50 613 patients porteurs d'un cancer de prostate, le taux de fracture était de 19,5 % à cinq ans chez ceux ayant reçu une hormonothérapie dans les six mois suivant le diagnostic contre 12,6 % chez les autres (p < 0,001) [39]. Les patients orchidectomisés ont un risque de fracture du col fémoral de 12 % à dix ans contre seulement 5 % pour la population générale [10]. La comparaison de 3 887 patients présentant un cancer non métastatique et traités par analogue de la LH-RH à 7 774 patients sans hormonothérapie met en évidence une augmentation significative du risque fracturaire associé à la dépri-vation androgénique (7,88 fractures pour 100 années-personnes dans le groupe sous analogues de la LH-RH versus 6,51 pour les autres patients ; p < 0,001) [44].…”
Section: Syndrome Métaboliqueunclassified
“…Bilateral orchiectomies are also associated with increased fracture risk in men with prostate cancer (31,32).…”
Section: Gnrh Agonists and Fracture Riskmentioning
confidence: 99%